Modified TR Band Application Technique for the Prevention of Hemostasis-Related Complications in Transradial Percutaneous Coronary Intervention (PCI) - Abda Ali; Muhammadong Muhammadong; Endah Sari Purbaningsih (International Journal Of Health Science, 2025)
The Trans Radial Band (TR Band) is a compression method applied to the radial artery following percutaneous coronary intervention (PCI). Prolonged TR Band removal duration may increase the risk of complications, while premature removal can lead to bleeding. This systematic review aims to evaluate the effectiveness of various modified TR Band application techniques in enhancing hemostasis and preventing vascular complications after transradial PCI. The study followed PRISMA guidelines, with literature searches conducted in PubMed, Scopus, and Google Scholar using specific keywords related to TR Band and its modifications. The results show that several modification techniques—including the use of rollers, slow deflation protocols, dual TR Band application, and hemostatic patches made from chitosan and potassium ferrate—generally improve hemostatic effectiveness, reduce hematoma incidence, and enhance patient comfort. However, limitations such as small sample sizes and the lack of long-term data remain challenges. Conclusion: Modified TR Band techniques are considered safe and effective, but larger-scale studies are still needed.